DAMPAK PASAR AL-MAHIRAH TERHADAP SOSIAL EKONOMI PEDAGANG KOTA BANDA ACEH - Hasbi; Saiful Bahgia; Hamdani (Lembaga Riset dan Inovasi Kreyat Center, 2023)
Al-Mahirah Market is built on two hectares of land. The market has six main buildings intended for poultry markets, meat markets, seasoning markets, vegetable markets, and fish markets, respectively. As a people's market and located on Jl. Syiah Kuala, Gampong Lamdingin, Kuta Alam District, Banda Aceh City. Al-Mahirah Market is a people's market resulting from the relocation of Peunayong Market, Kartini Market, and SMEP Market. This study aims to find out the perception of traders towards the development of Al-Mahirah Market and to determine the socioeconomic impact on these market traders. This research method is survey research using a quantitative descriptive analysis approach. The impact of Al-Mahirah Market on the socioeconomics of traders varies according to the perception of the trader used as a sample. Traders' perception of social impact is 62% casual and 18% have a good impact and as many as 20% give a bad perception of the impact experienced by traders. Labor Absorption, which is the capacity of the number of traders accommodated in the Al-Mahirah market in addition to traders relocated from the old market, which is 8.31%, the construction of Al-Mahirah Market provides a good map in facilitating new jobs for the residents of Banda Aceh City. Economic conditions based on the income of traders have not been able to have a significant impact on the development of Al-Mahirah Market, this is evidenced by the fact that most 75% of traders of medium income and 21% of traders have low incomes. The average economic condition of the market trader is based on income ranging from IDR1,500,000 to IDR2,500,000 per month and as many as 21% of traders have incomes below IDR1,500,000 per month.